Cavitation noise suppression in automotive heat pumps via vapor-doped supercavitation - Li Hu; Yachao Qin; Bing Ruan; Yeqing Wan; Bo Wang; Ruili Tian; Ni Quan (PLoS ONE, 2025)
Aiming at two-phase flow-induced noise of refrigerant in automotive heat pump air conditioner, the influence of the changes of pressure, flow rate and gas-phase volume fraction on the acoustic radiation produced by refrigerant in the process of phase change of electronic expansion valve is analyzed by constructing the refrigerant cavitation model and acoustic radiation model. It is found that the sudden pressure drop of the refrigerant leads to the phase change, forming the cavitation phenomenon, which in turn generates noise. Through CFD numerical simulation, the characteristics of the flow field distribution under different working conditions are explored, and the correlation between thermodynamic parameters and acoustic parameters is revealed. In order to reduce the noise, proposing vapor-doped supercavitation optimization strategy to study the influence of the structural parameters of the vapor-doped components on cavitation and noise, and the key structural parameters are optimized by the response surface methodology, and the peak sound pressure level is reduced by 9.95 dB, and the effective sound pressure level RMS is reduced by 0.79 dB. The results show that this component significantly reduce the SPL, which provides a theoretical basis and practical guidance for the noise reduction design of automotive heat pump air conditioner.